Pharmacological Manipulation of Shoaling Behavior in Zebrafish - Shams, Soaleha; T. Gerlai, Robert (Current Psychopharmacology, 2016)
Background: The zebrafish has been a favorite of developmental biologists and geneticists for decades, however, recently, it has gained popularity among behavior researchers too. The reason for the popularity of this species is that while it is a simple vertebrate, it possesses numerous features that make it translationally relevant. Objective: Social interaction is an essential component of human as well as zebrafish behavior; yet, the biological mechanisms underlying social behavior and its dysfunction remain poorly understood in both species. This review focuses on pharmacological manipulation of social behavior in zebrafish, studies where the ultimate goal is to understand the psychopharmacology of human behavior. Methods: We focused specifically on quantification of social interaction, specifically shoaling, in zebrafish, and compared it to rodent literature where appropriate. If no social studies exist for specific classes of compounds in zebrafish or if other behaviors may help with interpretation of social responses, we also highlighted non-social behaviors (locomotion, anxiety, etc). Results: We discussed findings on the effect of exposure of zebrafish to alcohol, psychostimulants, depressants and other drugs of abuse. Comparison of studies that have quantified and manipulated zebrafish social behavior of either single zebrafish or groups of zebrafish high-light both growth and gaps in this rapidly evolving field. Conclusion: Although new in psychopharmacology research, the zebrafish will be an important tool with which analysis and modeling of human social behavior and disorders involving social abnormalities including Fetal Alcohol Spectrum Disorders, Autism spectrum disorders, and Schizophrenia may be facilitated.
Keywords: Zebrafish